2015
DOI: 10.1002/acn3.185
|View full text |Cite
|
Sign up to set email alerts
|

Variants associated with Gaucher disease in multiple system atrophy

Abstract: ObjectiveGlucocerebrosidase gene (GBA) variants that cause Gaucher disease are associated with Parkinson disease (PD) and dementia with Lewy bodies (DLB). To investigate the role of GBA variants in multiple system atrophy (MSA), we analyzed GBA variants in a large case–control series.MethodsWe sequenced coding regions and flanking splice sites of GBA in 969 MSA patients (574 Japanese, 223 European, and 172 North American) and 1509 control subjects (900 Japanese, 315 European, and 294 North American). We focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
81
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 36 publications
0
81
0
Order By: Relevance
“…GBA mutations have been associated with different alpha-synucleinopathies, PD, Lewy Body Dementia and, recently, multiple system atrophy type C [3,4] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…GBA mutations have been associated with different alpha-synucleinopathies, PD, Lewy Body Dementia and, recently, multiple system atrophy type C [3,4] .…”
mentioning
confidence: 99%
“…PD patients with GBA1 mutations cannot be discriminated from idiopathic PD (iPD) [4] . Moreover, fluorodopa PET or SPECT with dopamine demonstrates the same asymmetric pattern in both conditions [4] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 They found a significantly increased odds ratio for GBA variants in MSA patients compared to controls. In fact, two patients with MSA had homozygous mutations in the GBA gene without a known clinical diagnosis of GD, while none of the controls had homozygous or compound heterozygous mutations.…”
Section: Glucocerebrosidase Genementioning
confidence: 99%
“…The prevalence of GBA mutations among patients with MSA has been studied by a few groups in recent years, and has yielded varied results. [19][20][21][22][23][24][25] Six studies have found no association between GBA mutations and MSA.…”
Section: Glucocerebrosidase Genementioning
confidence: 99%